Laboratory Animal Allergy (LAA) among the animal facilities’ workers in a research institute: A clinical survey - Heng, Pei Pei (2019)
Research animal facilities had been identified as a risky environment for the development of Laboratory Animal Allergy (LAA) among the exposed workers. The risk degree is in parallel with the nature of contact, intensity of exposure and individual susceptibility. Early recognition of LAA via active clinical surveillance is imperative before it progresses into occupational asthma with chronic disability. This study aimed to determine the prevalence of LAA among animal facilities’ workers in Institute for Medical Research, Malaysia together with its associated exposure or environmental risk factors. This cross-sectional study recruited a total of 87 workers exposed to animal allergen and 87 control subjects. Self-administered LAA questionnaire contained details of occupational and socio-environmental history as well as lung function test (spirometry) were employed as study tools. Statistical analysis were performed using SPSS version 20, utilizing descriptive analysis , cross tabulation, independent t-test ,Mann Whitney U-test and Multivariable Logistic Regression (MLR).More than half of the exposed subjects were reported at least one LAA symptoms (58.6%) and declined ling function (56.3%). Upper respiratory symptoms were the most prevalent LAA symptoms (49.4%). There was significant association between the reported symptoms and abnormal lung profile (p<0.05). In term of lung function values, the mean FEV1, median FVC and mean FEV1/FVC were significantly lower among the exposed group compared to the control group (p<0.001). MLR substantiated that atopic workers, smokers and those did not comply to full PPE regularly upon animal contact were more likely to develop LAA. LAA is an acknowledged occupational hazard. Therefore knowing the existing prevalence and its risk factors to design an effective LAA prevention program consisted of exposure avoidance as well as exposure reduction which combines the engineering control, administrative control and PPE is of paramount importance.